Pluralism in Practice: Creative Assessment for Deep, Inclusive, and Joyful Learning - Rozanski, Chelsea; Hackl, Vienna (Imagining SoTL, 2026)
How can assessment be reimagined to better support student creativity, critical thinking, and well-being? This paper argues that innovative, pluralistic strategies offer powerful, but often underutilized, pathways for deep learning in higher education. Drawing on examples from interdisciplinary university classrooms, it demonstrates how creative formats such as photography, food-making, visual arts, and performance enable students to showcase their understanding in culturally relevant, multimodal, and intellectually rigorous ways. Grounded in educational pluralism, Universal Design for Learning, and equity-focused pedagogy, the paper contends that creative assessments need not replace conventional methods; rather, they can complement and strengthen them by broadening what counts as valid evidence of learning. The paper also addresses common misconceptions about creative assessment—including concerns about consistency, scalability, and disciplinary fit—and illustrates how transparent guidelines, scaffolded preparation, and choice can uphold fairness while expanding student agency. By reframing assessment—both formative and summative—as a relational and meaning-making practice, the authors invite educators to see creativity not as an exception, but as an integral dimension of inclusive, high-quality teaching. Ultimately, this paper offers both conceptual framing and practical strategies for reimagining assessment as a space of justice, care, and shared intellectual discovery.